Military justice handbook - Paphiti, Anthony, (Anthony Steven), 1952- (Havant : Howgate Publishing, 2021)
'Covering every aspect of the Service Justice System (SJS) in the United Kingdom, this book is designed as a road map sufficiently detailed to qualify as a go to guide, as the law and relevant policy of the SJS is complex and often difficult to find. Practitioners can now turn to the Handbook for guidance on any Service Justice topic. The book includes Summary Hearing, Administrative Action, as well as the Summary Appeal Court, and of course, the Court Martial, and an explanation of the appeal avenues open. The civilian and military legal practitioner (or indeed Service person) must understand this dynamic in order to fully appreciate how the system works holistically. Drafted with a non-legal audience in mind, no single publication brings together law, policy and (importantly) the nuances of the Service Justice System like this book. Readers are informed of the subsequent consequences on them or their client where they are subject to service discipline. Designed especially for military lawyers of all armed Services, civil servants working within the Service Justice System, commanding officers, unit discipline staffs and civilian legal practitioners advising Service personnel involved with Court Martial advocacy, Service Complaints, inquiries or administrative action.'
Includes bibliographical references and index.
Keywords: Courts-martial and courts of inquiry -- Great Britain; Military offenses -- Great Britain; Military law -- Great Britain